Training on Utilizing Used Goods into Educational Teaching Aids - Eni Fatimah; Wulansari, Nidia; Nabillah, Rokhmatun; Muhaimin, A Nur; Nada, Ikatun; Soraya, Nabila Rizka (Jurnal Pengabdian Kepada Masyarakat Untukmu Nusantara, 2025)
One of the challenges in mathematics learning is the low mastery of basic multiplication of 1-10 among elementary school students. The purpose of this study was to develop and utilize recycled materials as innovative learning aids and environmentally friendly teaching aids to improve students' understanding of basic multiplication concepts. The methods used included identifying students' needs, creating teaching aids from recycled materials, and teaching students and teachers how to use these aids. The results of the study show that the use of teaching aids made from recycled materials can significantly increase students' motivation to learn and their understanding of basic multiplication concepts. In addition, the use of recycled materials also contributes to the development of creativity and critical thinking in the classroom. Therefore, this innovation can be an effective alternative to improve the mathematics learning process in elementary schools.